2005
DOI: 10.1038/sj.ejcn.1602162
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a colour food photography atlas as a tool for quantifying food portion size in epidemiological dietary surveys

Abstract: Objective: To test the validity of a colour food photography atlas for quantifying portion size eaten compared with weighed foods. Design: The colour food photography atlas was prepared by cooking, weighing and taking digital photographs of three portion sizes of 434 foods and beverages typical of the Italian diet. Subjects and interventions: In all, 448 male and female volunteers aged 6-60 y from a wide variety of social backgrounds completed 9075 assessments of food portions eaten at lunch and dinner in rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
128
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(143 citation statements)
references
References 20 publications
11
128
2
2
Order By: Relevance
“…The online food diary required participants to select items for each food eaten at breakfast, lunchtime and dinner plus any snacks consumed. All food items were associated with photographs of three portion sizes of foods typical of the Italian diet (Turconi et al, 2005). For the analyses, only items which referred to red meat were selected.…”
Section: Methodsmentioning
confidence: 99%
“…The online food diary required participants to select items for each food eaten at breakfast, lunchtime and dinner plus any snacks consumed. All food items were associated with photographs of three portion sizes of foods typical of the Italian diet (Turconi et al, 2005). For the analyses, only items which referred to red meat were selected.…”
Section: Methodsmentioning
confidence: 99%
“…Turconi et al (23) assessed the validity of food photographs in the estimation of food intake by children, adolescents and adults and also observed that there were no statistically significant differences in the identification of portion size in food photographs according to sex, age Cream of wheat 77 64 87 Beans 77 64 87 Lasagne 75 63 85 Cream cheese 75 63 85 Ground meat 74 62 84 Grated carrot 74 62 84 Fish 74 62 84 Yam 69 56 80 Watercress 68 55 79 Margarine 67 53 78 Pudding 66 53 77 Guava jam 63 50 75 Liver 61 47 74 Beef stew with vegetables 60 46 72 Chicken 52 38 65 Pineapple 47 34 61 Porridge 43 31 57 Chocolate powder 40 28 53 Tomato 29 18 43 *Polenta is a typical Brazilian dish made of cornmeal boiled in water with salt.…”
Section: Discussionmentioning
confidence: 99%
“…In our study we used food photographs that were originally developed for use in adults (15,16) and have been demonstrated to be useful in estimating portion sizes in adult populations. A number of studies have shown that children can use food photographs to adequately describe food portion sizes (17,18) . Foster et al (19) showed that children reporting portion sizes using adult food photographs overestimated their intake compared with using age-appropriate tools being developed by researchers.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%